Analysis of fine motor tests in five- to six-year old children - Kalar, Živa (Kinesiologia Slovenica, 2003)
The purpose of this research was to state the condition of clumsiness in five-to six-year-old children, to track down those whose results differ significantly from the average, and to find out whether there exist statistically significant differences in fine motor tests with regard to the children's sex. The data were obtained from eight fine motor tests performed on a sample of 30 five- to six-year-old girls and boys from four Slovenian kindergartens. The battery of tests is simple, the time needed for testing of each participant was 8 to 10 minutes. Data were processsed at the Ljubljana Faculty of Sport by the statistical SPSS programme, using the Frequencies subprogramme and the t-test. Within our sample, we established that the results children achieved were far below the average as follows: 7% of children three tasks at least, 28% of children in one task, and 13% of children in two tasks. Only 52% of children achieved expecetd, normal results in all the tasks. This research has shown that the results do not statistically differ in regards to children' sex.
Keywords: fina motorika; meritve; motorični testi; motorika; predšolski otroci; športna vzgoja; t-test